A construção simbólica na nação nos livros escolares no Moçambique Pós-Colonial (1975-1990) - Mindoso, André Victorino (2012)
This dissertation aims at analyzing the Mozambican Nation’s construction process during the post-colonial period (1975-1990) by investigating as its empirical source school books produced and divulged at the time It is therefore in a very direct way an analysis of school books used in the first grades of public primary schools namely 2nd 3rd 4th 5th and 6th grades Keeping a distance from essentialist conceptions the investigation tackles the concept of nation as a symbolically-devised political community involving people that independently from empirical characteristics establish solidarity-based ties among themselves supported by a past rich of experiences which will weld them as a unique group that will step beyond anything to express its will – cultivated by an elite – of going on living together in a geographically-established supposedly-free space Following this trail the upshot suggests that during pre-colonial time the Mozambican state reveals a symbolic process of erection of a nation that was trying with all its strength to keep itself apart from a fanciful socially-inclined body of ideas that dominated colonial life in its traditional ways That road was taken by the dominating elite headed by the former military decolonization movement the FRELIMO which by using the monopoly that it held over the process of production and divulging of educational contents such as school books had the opportunity to use them as disseminating agents of its ideas and apprehension of the world With the books FRELIMO tried to legitimate itself as a “dignified” leader of the people by means of a strategy bound on a universal approach to its experiences and auto-images directed to all as if FRELIMO and the people was the same “unit” Following that discursive trail daily actions of decolonization struggles were seen as “mythical” reference instances that by attitudes and behavior should be considered an “ideal pattern” that should inspire the new generation of Mozambicans At the same time FRELIMO claimed to itself the privilege of symbolically defining what in its interpretation should characterize the Mozambicans namely that they cultivated the worker’s habitus the warrior’s disposition exaltation of collective life and a great disposition for discipline and obedience.